Religious tolerance: the key between One ASEAN One Community - Talib, Ahmad Tarmizi; Gill, Sarjit S.; Muhamat @ Kawangit, Razaleigh; Kunasekaran, Puvaneswaran (Marsland Press, 2013)
Although the people in ASEAN countries comprise diverse ethnic groups and religions, there exist opportunities to develop one ASEAN Community through religious tolerance. The purpose of this paper is to propose religious tolerance as one of the keys in building “One ASEAN One Community”. This is based on a study conducted on the level of tolerance, which could help Malaysia address its religious issues in the context of a multi-religious society. The situation in Malaysia is quite similar to many other ASEAN countries. Malaysia, Thailand and Indonesia seem to be having a number of inter-religious conflicts and although these cases may not be representative of a large segment of the population, it is still alarming and calls for a duly appropriate and serious response.